Structural characteristics and field electron emission properties of carbon nanotubes synthesized from waste cooking palm oil - Falina, A.N.; Suriani, A.B.; Azmina, M.S.; Salina, M.; Dalila, A.R.; Nor, R.M.; Rusop, M. (2012)
In this work, we studied the effect of two different catalyst; nickel (Ni) and cobalt (Co) nitrate on structural characteristic and field electron emission properties of carbon nanotubes (CNT). Thermal chemical vapor deposition method and bio-hydrocarbon precursor namely waste cooking palm oil (WCPO) were utilized for the production of CNT. The surface morphologies of CNT were analyzed using field emission scanning electron microscopy while the crystallinity and the purity of CNT were analyzed using micro-Raman spectroscopy and thermogravimetric analysis. It was found that the density of CNT synthesized by the two catalysts was similar, but the diameters and crystallinity of the CNT synthesized by Ni catalyst were smaller and better as compared to Co catalyst. The field electron emission (FEE) of CNT synthesized by Ni catalyst also demonstrated lower turn-on and threshold field of 6.21 and 7.71 VÎ¼m-1 at 1 Î¼Am-2 and 10 Î¼Am-2 respectively and maximum current density of 0.132 mAm-2. The FEE measurement confirmed that the structural and crystallinity difference could significantly affect the electron emission properties of the CNT. This work shows the potential of catalytic decomposition of WCPO using Ni catalyst which outperformed Co in growing CNT towards field emission devices. Â© 2012 Penerbit UTM Press. All rights reserved.